190 L-Arginine upregulates aquaporin-3. (7th December 2018) - Zhu, C; Ye, J; Bazer, F; Johnson, G; Bai, Y; Yang, J; Chen, Z; Jiang, Z; Wu, G
Abstract: Dietary supplementation with L-arginine (Arg) has been shown to increase the volume of amniotic and allantoic fluids in gestating swine. The present study was conducted with porcine trophectoderm (pTr2) cells to test the hypothesis that Arg upregulates the expression of aquaporin 3 (AQP3) that is essential for implantation and development of blastocysts. The pTr2 cells were cultured in customized Arg-free Dulbecco's modified Eagle's Ham medium (DMEM) containing 0.00, 0.25, 0.50, or 1.00 mM Arg. N ω -nitro-L-arginine methyl ester hydrochloride [L-NAME, an inhibitor of nitric oxide synthase (NOS)] was used to inhibit the NO pathway. An activator (Forskolin) of cyclic adenosine monophosphate (cAMP) or an inhibitor of cAMP-dependent protein kinase (H-89) was used to determine a role for the cAMP signal pathway. AQP3 was expressed abundantly in pTr2 cells at both mRNA and protein levels. Compared with the control (0.00 mM Arg), 0.50 mM Arg increased ( P < 0.05) water transport by pTr2 cells as determined using Ussing chambers. Arg (0.50 mM) also up-regulated ( P < 0.05) AQP3 expression and increased NO synthesis in pTr2 cells ( P < 0.05). However, L-NAME reduced ( P < 0.05) NO synthesis, AQP3 expression and water transport by pTr2 cells. In addition, Arg (0.50 mM) increased ( P < 0.05) increased concentrations of cAMP and phosphorylated protein kinase A (PKA) and cAMP-response element binding protein (CREB). These effects of Arg were mimicked ( P < 0.05) by Forskolin ( P < 0.05), but inhibited ( P < 0.05) by H-89. Collectively, these results indicate that Arg increases transport of water by pTr2 cells by up-regulating AQP3 expression via NO- and cAMP-dependent mechanisms. (Supported by USDA-NIFA and NSFC) *Correspondence: g-wu@exchange.tamu.edu or jiangzy@gdaas.cn